2021
DOI: 10.5306/wjco.v12.i7.544
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of acquired resistance of BRCA1/2-driven tumors to platinum compounds and PARP inhibitors

Abstract: Molecular pathogenesis of tumors arising in BRCA1/2 germ-line mutation carriers usually includes somatic inactivation of the remaining allele of the involved gene. Consequently, BRCA1/2-driven cancers are sensitive to platinum-based therapy and poly (ADP-ribose) polymerase inhibitors (PARPi). Long-term exposure to these drugs may result in the emergence of secondary BRCA1/2 mutations, which restore the open-reading frame of the affected allele. This platinum/PARPi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
8
0
3
Order By: Relevance
“…Functional tests have an obvious advantage, as they evaluate the genuine activity of HR and can be applied to both chemonaive and pretreated tumors. Indeed, HR proficiency is often rescued during therapy courses through the second mutation restoring the open reading frame of BRCA1/2 or similar genes or by other bypass mechanisms [ 70 ]. The genomic scars described above remain predictive for HRD during the treatment course, even when the actual sensitivity to PARPi or platinum compounds is lost [ 50 ].…”
Section: Homologous Repair Deficiency (Hrd)mentioning
confidence: 99%
“…Functional tests have an obvious advantage, as they evaluate the genuine activity of HR and can be applied to both chemonaive and pretreated tumors. Indeed, HR proficiency is often rescued during therapy courses through the second mutation restoring the open reading frame of BRCA1/2 or similar genes or by other bypass mechanisms [ 70 ]. The genomic scars described above remain predictive for HRD during the treatment course, even when the actual sensitivity to PARPi or platinum compounds is lost [ 50 ].…”
Section: Homologous Repair Deficiency (Hrd)mentioning
confidence: 99%
“…Эти клетки, в отличие от нормальных, не способны репарировать двунитевые разрывы ДНК, поэтому они достаточно быстро накапливают критическую массу мутаций в онкогенах и супрессорных генах и подвергаются злокачественной трансформации. В то же время BRCA1/2-ассоциированные опухоли демонстрируют исключительную чувствительность к целому ряду терапевтических агентов [9].…”
Section: препараты с одинаковым принципом действияunclassified
“…В целом, BRCA1/2ассоциированные опухоли действительно демонстрируют очень высокую чувствительность к достаточно широкому спектру цитостатических препаратов, что подтверждается результатами многочисленных клинических наблюдений [11]. Примечательно, что адаптация опухолевых клеток к воздействию как PARP-ингибиторов, так и BRCA1/2-специфических цитостатиков, происходит по идентичному механизму, подразумевающему восстановление функции BRCA1/2 [9]. Именно поэтому в случае лечения рака яичников PARP-ингибиторы назначаются только для платиночувствительных разновидностей данного заболевания, а пациентки, у которых возникла резистентность к данному классу лекарственных препаратов, демонстрируют отсутствие эффекта от последующей химиотерапии [14].…”
Section: препараты с одинаковым принципом действияunclassified
“…Studies on BRCA1 -mutated ovarian carcinomas demonstrated the persistence of a small fraction of BRCA1-proficient cells even in chemonaive tumors; these cells rapidly repopulate tumor mass during the first weeks of platinum-based therapy thus explaining the phenomenon of inevitable emergence of platinum-resistance [ 78 , 79 ]. Therefore, it is potentially error-prone to evaluate the efficacy of BRCA1/2 -specific therapies in the pretreated patients, as the tumors rapidly lose their target and, therefore, adapt to the pressure of platinum compounds or PARPi [ 80 82 ].…”
Section: Acquired Resistance To Brca1/2 -Specifc Therapymentioning
confidence: 99%